Optimizing Profitability in a Sustainable Fashion MSME: A TOC Approach to Third-Party Production - Muhammad, Rahma Nazila (Indonesian Accounting Research Journal, 2025)
This study examines profit optimization in a sustainable fashion MSME in Indonesia that operates under a third-party production model. Using a qualitative single-case design with supporting quantitative data, it applies the Theory of Constraints (TOC) to identify and address systemic limitations. Contrary to conventional views that highlight production constraints in outsourced MSMEs, this study finds stable operations with consistent lead times and no fulfillment delays. Instead, the primary constraints are both external (marketing effectiveness, liquidity cycles, and inventory coordination) and internal (informal financial practices, unstructured budgeting, and opaque cost tracking). Using TOC’s Five Focusing Steps, the study proposes targeted interventions including campaign synchronization, structured cost allocation (e.g., fixed salary, R&D, and profit-sharing), and improved restocking coordination. These measures aim to enhance throughput and stabilize profit margins. This study also highlights the importance of iterative constraint monitoring through simple KPI tracking to anticipate future bottlenecks and support scalable growth. By contextualizing TOC in a decentralized, resource-limited setting, this study contributes to the limited empirical literature on constraint-based management in sustainable outsourcing models. It also provides practical insights for MSME owners, third-party partners, consumers, financial institutions, and policymakers to improve profit resilience, financial clarity, and demandresponsiveness without requiring capital-intensive expansion.